Association of processes of primary care and hospitalisation for people with diabetes: A record linkage study. Issue 2 (May 2015) - Comino, Elizabeth Jean; Islam, MD Fakhrul; Tran, Duong Thuy; Jorm, Louisa; Flack, Jeff; Jalaludin, Bin; Haas, Marion; Harris, Mark Fort
Highlights We explore the association between diabetes primary care processes and hospitalisation. Implementing recommended diabetes care is associated with reduced hospitalisation. Review of, and not just preparation of, management plans is required. Access to quality primary care provides alternatives to hospital presentation. Hospital avoidance programmes must support a strong primary care sector.